PENGARUH MEDIA DIORAMA BERBANTUAN QR CODE TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SDN 060932 MEDAN AMPLAS - Wulandari; Yusra Nasution; Lala Jelita Ananda; Husna Parluhutan Tambunan; Suyit Ratno (STKIP Subang, 2026)
This study aims to determine the effect of the use of QR Code-assisted diorama media on the learning outcomes of social studies of grade V students of SDN 060932 Medan Amplas. This study uses a quantitative approach with Quasi Experimental Design in the form of Nonequivalent Control Group Design in the even semester of the 2025/2026 Academic Year. The research sample amounted to 52 students consisting of 26 students in class V-A as the experimental class and 26 students in class V-B as the control class. The data collection technique uses validation questionnaires, learning outcome tests, and documentation. Data analysis uses analytical prerequisite tests which include normality tests and homogeneity tests, as well as hypothesis tests. The results showed that the pretest and posttest data in the experimental class and the control class were normally distributed based on the Shapiro-Wilk test with a significance value of > 0.05 and had a homogeneous variance based on the Levene test with a significance value of 0.107 (> 0.05). The average posttest score of the experimental class was 84.04 higher than that of the control class of 62.88. The results of the t-test (Independent Sample T-Test) obtained a Sig. (2-tailed) value of 0.000 (< 0.05), so that H₀ was rejected and Hₐ was accepted. Thus, the use of QR Code-assisted diorama media has a significant effect on the learning outcomes of IPAS students in grade V of SDN 060932 Medan Amplas. Based on the results of the study, it is recommended that teachers use QR Code-assisted diorama media as an alternative to innovative learning media.